IMPROVING STUDENTS’ ABILITY IN WRITING PROCEDURE TEXTS BY USING SHORT VIDEOS - TANEO, JUFRIANTI MARSALINA; BERA, LAURENSIUS KIAN; KOLO, CLEMENS (Academic Journal of Educational Sciences, 2023)
This research is entitled “Improving Students’ Ability in Writing Procedure Texts by Using Short Video”. The purpose is to know whether or not the use of short video is effective in improving the student’s ability to write procedure text, and this research was classified as action research. It was done in two cycles. The research was done with 30 students in third-semester students of the English Study Program of Nusa Cendana University in the academic year 2023/2024. The data obtained during the research were qualitative and quantitative data. The qualitative data were in the form of an observation checklist while the quantitative data were in the form of the students' scores. The subject was taught by a short video for two cycles and then the writer collected their data through a test. The result shows that the mean of the post-test in cycle two is higher than that of the test and post-test cycle one, which indicates that there is a significant increase in students’ writing, The mean of the pre-test was 63.16 and it increased to the post-test cycle one to become 74.16, the post-test cycle two also increased become 87.17. In other words, the alternative hypothesis which says, Improving Students’ Ability in Writing Procedure Texts by using Short Video is effective. Therefore, teachers of English are suggested to use short videos in teaching English, especially procedural text.